Can Plants’ Ability for DNA Repair and Stress Defense be Used against Patients’ Circulating Tumor Cells? - C.D. Volko; U.D. Rohr (Journal of Pharmacy and Nutrition Sciences, 2015)
Introduction: It was suggested that specific plants may reduce cancer's resistance to chemotherapy. Resistance inhibits apoptosis, as well as other fundamental anti-cancer protective mechanisms. Soy bean has been found to reduce cellular stress and repair DNA damage caused by drought or parasites, and can transfer this defense mechanism to other plant species as well. The aim of this study is therefore to conduct a systematic comparison of the effect of soy bean formulation (FSWW08) on gene expression in in vitro human breast cancer cell line, and in in vivo in blood circulating tumor cells (CTC), after oral consumption of FSWW08 by patients suffering from breast-, ovarian-, and prostate cancer. Method: In vitro gene expressions studies were conducted with the human breast cancer cell line BT-474 that was exposed to doxorubicin or FSWW08, either alone or in combination. Ovarian-, prostate-, and breast cancer patients received FSWW08 for 30 days. CTC were extracted from their blood according to an established protocol. Gene expression evaluations were conducted before and after treatment. Results: In vitro, the multi-drug resistance (MDR) protein was reduced by FSWW08, but was increased by doxorubicin. The combination of FSWW08 and doxorubicin, however, showed a protective effect against the increase of MDR in physiologic concentrations, increased, however, also in high experimental concentrations of both agents. The expression of several cancer-related protective genes, such as tumor suppressor factors p21, p38 and p53, was improved by FSWW08 in vitro and in vivo, which helped cell differentiation and new tissue formation. Additionally, the BAX/Bcl2 ratio was improved, in vitro, as well as gene expression of estrogen receptor beta, NF-κB, MAP kinase, c-JUN, and matrix metalloproteinase 9, together with an increase of VEGF expression in vivo in CTC. Conclusion: It was demonstrated that FSWW08 improved the gene functions related to DNA repair and stress in human blood CTC and resistance marker, in vitro, when applied in combination with doxorubicin. As such, larger in vitro and in vivo clinical studies that investigate single botanical compounds from other plants, are warranted.